Machado de Assis no Jornal das Famílias: um estudo sobre a jovem escrita machadiana - Januário, Soraya Vieira (2023)
Machado de Assis wrote and published his first short story in 1858 called “Três Tesouros Perdidos”, in 1862 he published “O país das quimeras” and only in 1864 he published stories again, such as “Frei Simão”, in the periodical “O Jornal das Famílias”, where he released more than half of his short story production. The main focus of this research is to study the young Machadian writing in short stories published in the “Jornal das Famílias” in 1863. Our object is to analyze the characteristics of his writing, the choice of themes by the writer, which would have influenced his initial production of stories and we also intend to investigate possible authorship attributed to Machado de Assis that still raise interest and controversy. In the “Jornal das Famílias,” the Bruxo signed with his name a few times, pseudonyms dominated Machado's writings from 1864 to 1878, the last year of the Journal. Could it be possible that the young and inexperienced Machado de Assis could have contributed to the magazine using other pseudonyms? This work also aims to present an overview of the pseudonyms used by the author to sign his stories during the initial publications of his career in the journal. The analysis undertaken in this study is based on the contributions of researchers and scholars such as: Massa (2009), Magalhães (1956), Galante de Souza (1955), Crestani (2009), Pinheiro (2007), among others, who bring through the information presented here, important aspects in Machado de Assis' short story writing in 1863 in the “Jornal das Famílias”.